Methylcobalamin promotes the differentiation of Schwann cells and remyelination in lysophosphatidylcholine-induced demyelination of the rat sciatic nerve - Nishimoto, Shunsuke; Tanaka, Hiroyuki; Okamoto, Michio; Okada, Kiyoshi; Murase, Tsuyoshi; Yoshikawa, Hideki (Frontiers in Cellular Neuroscience, 2015)
Schwann cells (SCs) are constituents of the peripheral nervous system. The differentiation of SCs in injured peripheral nerves is critical for regeneration after injury. Methylcobalamin (MeCbl) is a vitamin B12 analog that is necessary for the maintenance of the peripheral nervous system. In this study, we estimated the effect of MeCbl on SCs. We showed that MeCbl downregulated the activity of Erk1/2 and promoted the expression of the myelin basic protein in SCs. In a dorsal root ganglion neuron–SC coculture system, myelination was promoted by MeCbl. In a focal demyelination rat model, MeCbl promoted remyelination and motor and sensory functional regeneration. MeCbl promoted the in vitro differentiation of SCs and in vivo myelination in a rat demyelination model and may be a novel therapy for several types of nervous disorders.